Treatment Of Landfill Leachate By Palm Oil Waste Carbon Copper-Oxide Nano Composite - Abu Bakar, Siti Nurwajihah (Universiti Sains Malaysia, 2018)
Landfill leachate contains large amount of organic and inorganic contaminants which is it hazardous and bring a tremendous impact towards the environment in surface water, groundwater and air. The landfill leachate needed to be treated to avoid from contamination of these hazardous composition born from the leaching process. In this studies, the treatment method that have been discussed was chemical physical process of adsorption. Thus, oil palm frond was used as precursor to produce the adsorption treatment in COD, colour and heavy metals removal from landfill leachate. The effectiveness of adsorption rate was studied based on the effects of impregnated ratio, temperature and time of carbonization by using H3PO4. In order to examine the adsorption rate was gained from iodine number test where the optimum impregnated ratio was 1:3 at 400oC for 1 hour respectively. The dosage and contact time was examined where the optimum dosage rate is 0.6g at 30 minutes. The activated carbon nanocomposite with Copper oxide was studied in this research to determine the performance in adsorption rate. Both Langmuir and Freundlich Isotherms could be used to describe the adsorption of COD, colour and heavy metals.